ANALISIS BEBAN KERJA PADA PT. BPR SUBANG GEMI NASTITI (PERSERODA) KANTOR PUSAT OPERASIONAL DI KOTA SUBANG - Ina Ratnamiasih; Widi Andini (Jurnal Riset Mahasiswa, 2023)
This study aims to find out how to analyze workload in an effort to improve employee performance. The research method used is a qualitative method. Data collection techniques used are observation, interviews, and literature study. Descriptive data analysis with workload calculations using the Nasa TLX approach. The results showed that the workload at PT. BPR Subang Gemi Nastiti is high. Factors that cause this are the company's target which is too high and the lack of number of employees in the marketing division. The recommendations put forward include providing training, increasing the number of employees, improving work methods for time efficiency, and improving the reward system to motivate employee performance